Virtual Reality for Traffic Safety Education in Elementary Schools - Vera Yuli Erviana; Oktomi Wijaya; Dwi Sulisworo; Rusydi Umar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Traffic safety education needs to be taught to children at an early age. Traffic safety training for children in a real-world environment has several challenges and difficulties. Letting children practice in the real traffic environment will expose them to potential hazards. The purpose of this study was to develop media promotion for traffic safety education using a virtual reality (VR) for elementary school students. Methods: This research design used the 4-D model (define, design, develop, and disseminate). Data were collected qualitatively by conducting FGDs and interviews, while quantitative data were collected by distributing questionnaires. Results: The traffic safety VR media tested 4 scenarios, namely: driving equipment, traffic lights, how to cross the road, and walking etiquette. The validity test results show that VR traffic safety is feasible to be used as learning media for elementary school students. Students and teachers responded positively to this media. The advantage of this media is that it is fun and interactive for children. Conclusion: Media promotion for traffic safety education using virtual reality can be applied in a wider scope in other elementary schools. Future research can develop more complex scenarios such as cycling, crossing railroad, and many more. The use of virtual reality (VR) in traffic safety training provides an immersive and interactive learning experience, which is more engaging compared to traditional methods.